The Handsome Man's De Luxe Cafe - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2014)
"The newest installment in the beloved and best-selling series. In this delightful fifteenth installment, Mma Ramotswe has her hands full both at home and in the office. To add to her current challenges, her devoted partner, Grace Makutsi, has decided to branch out on her own and open The Handsome Man's De Luxe Cafe. But even "Miss 97 Per Cent" can't quite meet all the demands of running a business--not to mention those that a lightning strike makes on her building. Eventually, she'll have to accept all the help she can get--even if it comes from a completely unexpected source"--